Peran Literasi Agama dalam Meningkatkan Maharah Qira’ah di SMP Pahlawan Nasional Kota Medan - Annisa Annisa; Haidarul Gholib Al-Ghozi; L’Niana Aulia Zuhri Dalimunthe; Sahkholid Nasution (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This study aims to deeply analyze the role of religious literacy in improving maharah qira'ah (reading ability) at SMP Pahlawan Nasional Kota Medan. Using a qualitative-descriptive approach, this study explores data thoroughly regarding students' ability to read the Qur'an and its relationship to the religious literacy program implemented at the school. Data collection methods include memorization and Qur'an reading tests, observation of reading abilities, and surveys to explore students' perceptions of the importance of religious literacy. The results show that the majority of students still require intensive guidance in reading the Qur'an. In each class, only a few students are able to read the Qur'an and pronounce Arabic correctly, although their fluency is still lacking. Most students are not able to read the Qur'an fluently, and some still struggle to distinguish hijaiyah letters. These findings indicate the need for a systematic and intensive religious literacy program to help students improve their maharah qira'ah skills. Additionally, a more personalized teaching approach is necessary to address the specific challenges students face in reading the Qur'an.